1999
DOI: 10.1002/stem.170055
|View full text |Cite
|
Sign up to set email alerts
|

Hemopoietic Progenitor Cell Mobilization and Harvest Following an Intensive Chemotherapy Debulking in Indolent Lymphoma Patients

Abstract: An in vivo purging with intensive debulking chemotherapy prior to peripheral blood progenitor cell (PBPC) collection may reduce the risk of tumor contamination of the harvest products; however, it is usually associated with a marked reduction in PBPC mobilization. These issues have been considered while designing an adapted version of the high-dose sequential regimen for patients with lymphoid malignancies and bone marrow involvement. To reduce tumor contamination risks, PBPC collection was postponed to the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…55 Dose-dependent decreases in potentially malignant CD19 þ cells have been noted when both CY and G-CSF are used for mobilization. 121 Although mobilization regimens that include chemotherapy have been noted to reduce the risk of tumor-contaminated cell collections in patients with MM or lymphoma, 20,30 there is considerable debate as to whether the cytoreductive effects of mobilization with CY and growth factors confer any survival benefit to the patient. Dingli et al 37 showed that the addition of CY to a G-CSF mobilization regimen did not significantly improve response rates or prolong the time to disease progression.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
See 4 more Smart Citations
“…55 Dose-dependent decreases in potentially malignant CD19 þ cells have been noted when both CY and G-CSF are used for mobilization. 121 Although mobilization regimens that include chemotherapy have been noted to reduce the risk of tumor-contaminated cell collections in patients with MM or lymphoma, 20,30 there is considerable debate as to whether the cytoreductive effects of mobilization with CY and growth factors confer any survival benefit to the patient. Dingli et al 37 showed that the addition of CY to a G-CSF mobilization regimen did not significantly improve response rates or prolong the time to disease progression.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
“…13,30,129 Although mobilization with chemotherapy results in successful stem cell collections in the majority of patients, obtaining adequate CD34 þ cells may be more difficult in patients with low-grade lymphoma than in most other patients who are candidates for auto-HSCT. 30,129 In addition, previous courses of chemotherapy and radiotherapy can adversely influence CD34 þ cell yields.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
See 3 more Smart Citations